Does the effect of one-day simulation team training in obstetric emergencies decline within one year? A post-hoc analysis of a multicentre cluster randomised controlled trial. (September 2017) - van de Ven, J.; Fransen, A.F.; Schuit, E.; van Runnard Heimel, P.J.; Mol, B.W.; Oei, S.G.
Abstract: Does the effect of one-day simulation team training in obstetric emergencies decline within one year? A post-hoc analysis of a multicentre cluster randomised controlled trial. J van de Ven, AF Fransen, E Schuit, PJ van Runnard Heimel, BW Mol, SG Oei Objective: To investigate whether the effect of a one-day simulation-based obstetric team training on patient outcome changes over time. Study design: Post-hoc analysis of a multicentre, open, randomised controlled trial that evaluated team training in obstetrics (TOSTI study).We studied women with a singleton pregnancy beyond 24 weeks of gestation in 24 obstetric units. Included obstetric units were randomised to either a one-day, multi-professional simulation-based team training focusing on crew resource management in a medical simulation centre (12 units) or to no team training (12 units). We assessed whether outcomes differed between both groups in each of the first four quarters following the team training and compared the effect of team training over quarters. Primary outcome was a composite outcome of low Apgar score, severe postpartum haemorrhage, trauma due to shoulder dystocia, eclampsia and hypoxic-ischemic encephalopathy. Results: During a one year period after the team training the rate of obstetric complications, both on the composite level and the individual component level, did not differ between any of the quarters. For trauma due to shoulder dystocia team training led to a significant decrease in the first quarter (0.06% versus 0.26%, OR 0.19, 95% CI 0.03 to 0.98) but in the subsequent quarters no significant reductions were observed. Similar results were found for invasive treatment for severe postpartum haemorrhage where a significant increase was only seen in the first quarter (0.4% versus 0.03%, OR 19, 95% CI 2.5–147), and not thereafter. Conclusion: The beneficial effect of a one-day, simulation-based, multiprofessional, obstetric team training seems to decline after three months. If team training is further evaluated or implemented, repetitive training sessions every three months seem therefore recommended.